THE CINEMATIC EXCELLENCY OF MRINAL SEN: A ANALYTIC STUDY OF AKALER SONDHANE (International Journal of Food and Nutritional Sciences, 2022)
Mrinal Sen, one of the most celebrated filmmakers of Indian cinema, has carved a distinctive niche for himself with his socially conscious and aesthetically compelling works. Known for his exploration of socio-political realities through an innovative cinematic lens, Sen’s films often serve as a mirror to the complexities of contemporary society. Among his significant works, Akaler Sandhane (1980) stands out as a profound commentary on the intersection of art, reality, and human suffering. The film, set against the backdrop of a famine-stricken village, blurs the lines between fiction and reality, offering a multi-layered narrative that reflects Sen’s mastery in storytelling and visual composition. By examining the film’s themes, narrative structure, technical brilliance, and its broader socio-cultural implications, this analysis aims to shed light on how Sen uses cinema as a tool to provoke thought and evoke empathy. Through this exploration, we seek to understand the elements that contribute to the timeless relevance of Akaler Sandhane and how it exemplifies Mrinal Sen's unparalleled contributions to the world of cinema.